Impact of Traffic Patterns on Trauma Response Prenotification [Letter] - Muttaqin MZ (Open Access Emergency Medicine)
M Zaenul Muttaqin Public Administration Study Program, Cenderawasih University, Jayapura City, IndonesiaCorrespondence: M Zaenul Muttaqin, Email mzaenul69@gmail.com